A comparison of lymphocytic thyroiditis with papillary thyroid carcinoma showing suspicious ultrasonographic findings in a background of heterogeneous parenchyma - Nam, Sang Yu (Ultrasonography, 2015)
PURPOSE: The aim of this study was to compare ultrasonographic features in patients with lymphocytic thyroiditis (LT) and papillary thyroid carcinoma (PTC) having suspicious thyroid nodule(s) in a background of heterogeneous parenchyma and to determine the clinical and radiological predictors of malignancy. METHODS: We reviewed the cases of 100 patients who underwent ultrasonography between April 2011 and October 2012, and showed suspicious thyroid nodule(s) in a background of heterogeneous parenchyma. Eight patients who did not undergo ultrasonography-guided fineneedle aspiration cytology (FNAC) and 34 cases of follow-up ultrasonography after initial FNAC were excluded. We compared the benign and malignant nodules in terms of their clinical and radiological factors. RESULTS: For the 58 nodules including 31 LTs (53.4%) and 27 PTCs (46.6%), the mean tumor sizes of the two groups were 0.96 cm for LT and 0.97 cm for PTC. A univariate analysis revealed that PTCs were more frequent in patients younger than 45 years and having microcalcifications than was LT. An independent predictor of PTC after adjustment was an age of <45 years. CONCLUSION: LT mimics malignancy in a background of heterogeneous parenchyma on ultrasonography. A young age of <45 years is the most important predictor of malignancy in this condition.